Helicobacter pylori virulence factors: relationship between genetic variability and phylogeographic origin - Aura M. Rodriguez (PeerJ Inc., 2021)
Background Helicobacter pylori is a pathogenic bacteria that colonize the gastrointestinal tract from human stomachs and causes diseases including gastritis, peptic ulcers, gastric lymphoma (MALT), and gastric cancer, with a higher prevalence in developing countries. Its high genetic diversity among strains is caused by a high mutation rate, observing virulence factors (VFs) variations in different geographic lineages. This study aimed to postulate the genetic variability associated with virulence factors present in the Helicobacter pylori strains, to identify the relationship of these genes with their phylogeographic origin. Methods The complete genomes of 135 strains available in NCBI, from different population origins, were analyzed using bioinformatics tools, identifying a high rate; as well as reorganization events in 87 virulence factor genes, divided into seven functional groups, to determine changes in position, number of copies, nucleotide identity and size, contrasting them with their geographical lineage and pathogenic phenotype. Results Bioinformatics analyses show a high rate of gene annotation errors in VF. Analysis of genetic variability of VFs shown that there is not a direct relationship between the reorganization and geographic lineage. However, regarding the pathogenic phenotype demonstrated in the analysis of many copies, size, and similarity when dividing the strains that possess and not the cag pathogenicity island (cagPAI), having a higher risk of developing gastritis and peptic ulcer was evidenced. Our data has shown that the analysis of the overall genetic variability of all VFs present in each strain of H. pylori is key information in understanding its pathogenic behavior.